RESPON PERTUMBUHAN DAN HASIL TANAMAN SELADA MERAH (Lactuca sativa L. var Red rapid) TERHADAP KOMPOSISI MEDIA TANAM DAN KONSENTRASI POC NASA - Ria Dilo Farenza (Universitas Islam Balitar, 2021)
This study aims to determine the influence of interaction, composition, concentration of planting media and the best liquid organic fertilizer on the growth and yield of red lettuce plants. This study used a randomized design of factorial groups. The first factor is M1: soil: chicken manure (1 : 1), soil M2: chicken manure: husk charcoal (1: 1: 1) and soil: chicken manure : sand (1: 1: 1). The second factor of NASA POC is 0 ml/liter of water, 2ml/liter of water, 4 ml/liter of water, 6ml/liter of water. The results showed that there were significant interactions in the treatment of planting media composition and NASA POC concentrations on plant height, number of leaves, total weight of fresh plants and consumption weight at harvest. The best treatment is the composition of the soil growing medium: chicken manure: husk charcoal (1: 1: 1) with a NASA POC concentration of 4 ml / liter of water.